A qualitative single-case study exploring the impact of a mentor and cohort on students’ academic and career decisions (Journal of Applied Learning and Teaching, 2022)
Exposure to research is known to play a positive role in undergraduate education. However, robust research responsibilities are oftentimes not formally incorporated into a student’s academic experience until master level studies. Further, a variety of intimidation factors often inhibit many undergraduate students from participating on a research team. In this case study, the research team evaluated a unique group of undergraduate researchers who matriculated to the same university after beginning to participate in research as concurrently enrolled students. Following matriculation, each student continued to participate in research throughout the entirety of their undergraduate studies. All of the study’s students were STEM majors and undertook this research, both prior to and following matriculation, in the same lab and under the same mentor. This arrangement removed many of the common barriers to students participating in undergraduate research, such as the intimidation of working with strangers, including graduate students, and unclear expectations for undergraduate lab students from faculty. Consequently, the unique circumstance presented in this work affords the opportunity to more fully explore the influence that a strong long-term mentor and extended participation in research have on students’ post-graduate decision making.